The wren, the wren : a novel - Enright, Anne, 1962- (W.W. Norton & Company, 2023)
"From Booker-prize winning author Anne Enright, an astonishing novel about the love between mother and daughter--sometimes fierce, often painful, but always transcendent. "Carmel had been alone all her life. She had been alone since she was twelve years old. The baby knew all this. They looked at each other; one life into another life, and the baby knew exactly how alone her mother had been." Nell--funny, brave and so much loved--is a young woman with adventure on her mind. As she sets out into the world, she finds her family history hard to escape. For her mother, Carmel, Nell's leaving home opens a space in her heart, where the turmoil of a lifetime begins to churn. And across the generations falls the long shadow of Carmel's famous father, an Irish poet of beautiful words and brutal actions. In this penetrating and beautifully written novel, Anne Enright luminously brings to life the essence of what makes a family survive the vicissitudes of life. The Wren, the Wren is a meditation on love: spiritual, romantic, darkly sexual, or genetic. A generational saga that traces the inheritance not just of trauma but also of wonder, it is a testament to the glorious resilience of women, by one of the greatest living writers of our age."--